Linear Equations - Solving by addition

I have tried to do this problem a minimum of 10 times and come up with different answers each time.

Solve the linear equation by addition:

4 (1-x) + y = 3

3 (1 - y) - 4x = -4y

4 -4x + y = 3

3 - 3y - 4x = -4y

4 -4x + y = 3

3 -4x - 3y = -4y

(-1) 3 -(-1)4x - (-1)3y = -4y (-1)

-3 +4x + 3y = 4y

__ 4 -4x + y = 3__

1 + 4y = 4y + 3

-3 -3

-2 + 4y = 4y

-4y -4y

-2 = 0

Though I have had other answers with y = 2/3, y = 1 and many more. I took a break from this last night hoping I would get a fresh look today but it didn't work.

Please help! I am stumped on this one.

Thank you!

Re: Linear Equations - Solving by addition

since the coefficient of x & y is same

so you can't solve this equation.................

thankyou...

Re: Linear Equations - Solving by addition

Thank you.

Just so I understand, because the equation has -4x and -4y, it can never be solved and I didn't need to go on and solve by addition. Just by looking at that would mean there is no solution?

3 -4x - 3y = -4y